A socially just transition through the European Green Deal? - Sebastiano Sabato; Boris Fronteddu (European Trade Union Institute (ETUI), 2020)
The aim of this working paper is to provide a preliminary assessment of whether the European Green Deal constitutes a suitable policy framework to combine environmental and economic objectives with the pursuit of social fairness, thus ensuring a just transition towards more sustainable economies and societies. Such an assessment appears particularly relevant in a period in which the EU and its Member States are figuring out how to redesign their economies and societies in order to cope with the unprecedented social and economic crisis triggered by the Covid-19 pandemic.
Keywords: 330; EU environmental policy; Sustainable development; coronavirus; working world; Justice; EU countries; EU-Umweltpolitik; Nachhaltige Entwicklung; Coronavirus; Arbeitswelt; Gerechtigkeit; EU-Staaten